Perlindungan Hukum Terhadap Orang-Orang Yang Ditahan Berkaitan Dengan Konflik Bersenjata Non Internasional Berdasarkan Hukum Nasional Indonesia - Zunnuraeni - (Fakultas Hukum Universitas Mataram, 2016)
Deprivation of liberty may not be avoided, and justified by law in both international armed conflict and non international armed conflict. Additional Protocol II and Common Article 3 of Geneva Convention regulate protection for detainee in relation to non international armed conflict. However some cases showed violation to international humanitarian law, particularly arbitrary deprivation of liberty. Some states use internir/administrative detention to justified detention out of criminal law, in such away that run the chance of arbitrary deprivation of liberty. Act Number 23/prp/1959 on The Establishment of State Emergency authorizes Military emergency Power to arrest and detain. Military Emergency situation is a non international armed conflict if it meet the international humanitarian law requirement. The authorization of military emergency power to detain shall appropriate with international humanitarian law. The result of this reseach shows that: (1) Rule of international armed conflict and non international armed conflict are regulated in Act Number 23/Prp/1959. The Act do not use non international armed conflict term but use military emergency term. In military emergency situation, Military Emergency Power have an authority to arrest and detain based on state security reason; (2) Rule of Detention by the Military Emergency Power in Article 32 Act Number 23/Prp/1959 do not agree with principle of protection in international humanitarian law because it do not appropriate with Rule 99 International Humanitarian Law on Prohibition to Arbitrary Deprivation of Liberty.